Analisa Kandungan Timbal (Pb) pada Minyak Sebelum dan Sesudah Penggorengan yang Digunakan Pedagang Gorengan Sekitar Kawasan Traffic Light Kota Medan Tahun 2012 - Rapotan Hasibuan; wirsal hasan; evi naria (Lingkungan dan Kesehatan Kerja, 2012)
Analysis of lead (pb) in cooking oils before and after frying that used by merchant at traffic light area of Medan city in 2012. Some fried food merchants located at the intersection of the highway near the traffic lights, where it was risk contaminated by lead resulting smoke emission vehicles. Lipophilic of lead could be attached to the cooking oils. This study was descriptive research, intended to know the levels of lead (Pb) in the cooking oils before and after fried that used fried merchants caused smoke pollution. The object of this study were 10 points cooking oils samples consist of 5 samples before and 5 samples after fried. The results of the study showed that there was one sample before frying cooking oils that were not eligible under the Regulation of BPOM RI No. HK.00.06.1.52.4011 2009, while the other four were eligible. For samples of cooking oils after fried, all points were not eligible. Behaviors of merchants at five intersections also was still not in accordance with the principles of food hygiene and sanitation in food processed  to avoid contamination of lead (Pb). It was recommended to the Medan City Health Department to coach and supervise the fried food trade that were found sold friend food in the highway intersections. Key words: cooking oils, lead, fried merchant, highway intersection